PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, HARGA DAN LABEL HALAL TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN SAMBAL LALAP DI SAMARINDA - Krisdayanti; Suyanto (University of Widya Gama Mahakam Samarinda, 2021)
This study aims to determine whether there is an influence between the variables of Product Quality (X1) Service Quality (X2), Price (X3) and Halal Label (X4) on Consumer Satisfaction (Y). The results of this study show that Product Quality (X1) and Price (X3) variables partially have an influence on Consumer Satisfaction (Y) while Service Quality (X2) and Halal Label (X4) variables partially have no effect on Consumer Satisfaction (Y) . Then based on the F test, the results obtained 63,934> 2,470 meaning that the variables of Product Quality (X1), Service Quality (X2), Price (X3) and Halal Label (X4) affect Consumer Satisfaction (Y). Then the value obtained is that the value of R2 (R Square) has an effective contribution of 0.729 (72.9%) which means that 4 variables in this study are Product Quality (X1) Service Quality (X2), Price (X3) and Halal Label (X4). has an effective contribution of 72.9% to Consumer Satisfaction (Y).